4He diffusion in specular hematite - Lippolt, Hans J.; Wernicke, Rolf Stephan; Boschmann Käthler, Werner (Physics and chemistry of minerals, 1993)
In order to test the chronometer qualities of speculante for the (U + Th)/He dating method, 4He release experiments by stepwise heating of two specularites from the Rimbach mineralization locality in the southern Vosgues (France) have been carried out. The diffusion coefficients define linear Arrhenius plots within a temperature interval of 250 to 830 °C, which is suggestive of volume diffusion. Extrapolation of the diffusion behavior to 20° C yields diffusion coefficients (D20 values) smaller than 10−26 [cm2 s−1] for both hematites with activation energies at 116 [kJ/mole]. The results of our study suggest that specularite is a very helium retentive hematite variety which is capable of quantitatively retaining radiogenic helium over geologic periods of time.
Im Titel ist die Zahl "4" hochgestellt
Gesehen am 01.03.2023